Managing workforce agility through bureaucratic leadership and organizational culture in public service mediated by psychological empowerment - Hernawaty Hernawaty; Muchlis Syahrani (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2022)
This study aims to analyze the influence of bureaucratic leadership and organizational culture in public service on workforce agility mediated by psychological empowerment in East Kalimantan. This is an explanatory survey of local government organizations/LGOs in East Kalimantan with an observation unit, consisting of 238 employees who were selected randomly. Data analysis was then carried out using the covariant SEM procedure. The results showed that workforce agility was influenced by leadership and organizational culture. Therefore, leaders who are able to maintain balance in local political dynamics, administrative demands, and running strategy execution are needed. This is because they can ensure the readiness of subordinates to participate in acceleration. Additionally, the organizational culture ensures the orientation of employees to workforce agility through an effective empowerment process. Psychological empowerment mediates the influence of bureaucratic leadership and organizational culture on workforce agility. Agility concept in the organization is one of the major focuses, and itsimplementation is a strategic and operational framework for public institutions. Integrating the idea of ​​agility, leadership, and workforce is a framework to design methods and taxonomies to set priorities for workforce agility in public institutions from a new public service perspective.